Influence of source electrode metal work function on polar gate prompted source hole plasma in arsenide/antimonide tunneling interfaced junctionless TFET. (1st April 2022) - Sharma, Samriti; Chaujar, Rishu
Abstract: Numerous studies have explored the impact of control gate and polar gate (PG) on the retention of hole and electron charge plasma to induce the source and channel region polarity in junctionless tunnel field effect transistor (JLTFET). However, PG is not the only one responsible for the retention of hole plasma in the p + prompted source but the hole plasma near the interface of source electrode metal (SEM) and p + prompted source (SEM/S) is influenced by the choice of SEM work function too. This paper features a comprehensive investigation of the mutual significance of PG and SEM work function on p + prompted source to study key analog characteristics of arsenide/antimonide tunneling interfaced hetero-material JLTFET (HJLTFET), which is unexplored in the literature otherwise. We have considered three metals—W (4.55 eV), Mo (4.65 eV), and Pd (5.3 eV) as the source electrodes in HJLTFET. For SEM work function lesser than p + prompted source (W and Mo), the Schottky contact is formed by the depletion of hole plasma near SEM and p + prompted source interface. This results in the immediate current inhibition at source to channel interface caused by an undesired movement of electrons en route to the Schottky interface. The Schottky tunneling phenomenon is considered by implementing the universal Schottky tunneling (UST) model to study the underestimated drain current of HJLTFET. However, the UST model becomes inconsequential for SEM work function higher than p + prompted source (Pd) as hole plasma is preserved by the ohmic contact formation.